Experimental Study of the Dynamic Behavior of Stabilised Marl with Lime - Lasheb, Micipsa; Melbouci, Bachir (Salehan Institute of Higher Education, 2025)
The variable characteristics of weathered marl cause engineering problems, particularly in geotechnics, and require in-depth studies to design structures. Where these characteristics are poor, lime is used to stabilize the soil. Experimental research is being carried out on various Tizi-Ouzou marls composed of different percentages of CaCO3. The aim is to study their behavior in the presence of quicklime and its impact on the evolution of their geotechnical characteristics to provide effective and economical solutions for stabilization. These marls are mixed with increasing percentages of lime and subjected to a series of tests in which cyclic shear is essential for simulating dynamic effects. The results obtained confirm the improvement in their geotechnical characteristics. On the one hand, interstitial pressures and cyclic deformations have decreased, thus avoiding the risk of liquefaction, subsidence, or settlement. On the other hand, cyclic stresses and resistances have increased, resulting in better resistance of these stabilized marls to dynamic stresses. Finally, the number of cycles required to reach failure has increased, thus reducing the risk of pavement damage. These results depend primarily on the percentage of CaCO3in the marl. Doi: 10.28991/CEJ-2025-011-01-09 Full Text: PDF